Expression of glypican 3 is an independent prognostic biomarker in primary gastro-esophageal adenocarcinoma and corresponding serum exosomes - Rahbari, Mohammad; Pecqueux, Mathieu; Aust, Daniela E.; Stephan, Holger; Tiebel, Oliver; Chatzigeorgiou, Antonios; Tonn, Torsten; Baenke, Franziska; Rao, Venkatesh Sadananda; Ziegler, Nicole; Greif, Helena; Lin, Kuailu; et al. (Journal of Clinical Medicine, 2019)
Exosomes are nano-sized membranous vesicles of endosomal origin that carry nucleic acids, lipids and proteins. The cargo of exosomes is cell origin specific and the release of these exosomes and uptake by an acceptor cell is seen as a vital element of cell-cell communication. Here, we sought to investigate the diagnostic and prognostic value of the expression of glypican 3 (GPC3) on primary gastro-esophageal adenocarcinoma (GEA) tissue (tGPC3) and corresponding serum exosomes (eGPC3). Circulating exosomes were extracted from serum samples of 49 patients with GEA and 56 controls. Extracted exosomes were subjected to flow cytometry for the expression of eGPC3 and GPC3 expression on primary GEA tissue samples was determined by immunohistochemistry and correlated to clinicopathological parameters. We found decreased eGPC3 levels in GEA patients compared to healthy controls (p < 0.0001) and high tGPC3 expression. This was significantly associated with poor overall survival (high vs. low eGPC3: 87.40 vs. 60.93 months, p = 0.041, high vs. low tGPC3: 58.03 vs. 84.70 months, p = 0.044). Cox regressional analysis confirmed tGPC3 as an independent prognostic biomarker for GEA (p = 0.02) and tGPC3 expression was validated in two independent cohorts. Our findings demonstrate that eGPC3 and tGPC3 can be used as potential diagnostic and prognostic biomarkers for GEA.